Comprehensive geriatric intervention in community‐dwelling older adults: a cluster‐randomized controlled trial - Yuya Watanabe; Yosuke Yamada; Tsukasa Yoshida; Keiichi Yokoyama; Motoko Miyake; Emi Yamagata; Minoru Yamada; Yasuko Yoshinaka; Misaka Kimura; for Kyoto‐Kameoka Study Group (Wiley, 2020)
Abstract Background In longevity societies, one of the most serious social issues is sarcopenia and/or frailty. Preventing them is important for maintaining independence and quality of life in the older population. This study investigated the effect of a self‐monitoring comprehensive geriatric intervention programme (CGIP) on physical function and muscle size in community‐dwelling older adults. We compared the effects of a CGIP using weekly class‐styled (CS) sessions and a home‐based (HB) programme. Methods The 526 participants were randomized into one of two groups (CS 251, HB 275) based on their residential districts. We conducted a 12 week CGIP, which consisted of low‐load resistance exercise, physical activity increments, oral function improvements, and a nutritional guide. All participants were encouraged to attend two 90 min lectures that included instructions on the CGIP. They were provided with exercise materials (triaxial‐accelerometers/pedometers, ankle weights, and elastic bands) and diary logs. The CS group attended 90 min weekly sessions and independently executed the programme on other days, whereas the HB group only received instructions on how to execute the programme. Physical functions, such as knee extension strength (KES), normal and maximum walking speed, the timed up‐and‐go test, and anterior thigh muscle thickness (MT), were measured and analysed using intention‐to‐treat analysis before and after the 12 week intervention. Results Of the 526 participants identified, 517 (CS 243 age 74.0 ± 5.4 women 57.2%, HB 274 age 74.0 ± 5.6 women 58.8%) were enrolled. Nine (CS 8, HB 1) were excluded from the analysis because they did not participate in the pre‐intervention measurements. Both interventions significantly improved KES (CS 18.5%, HB 10.6%), normal walking speed (CS 3.7%, HB 2.8%), and MT (CS 3.2%, HB 3.5%). Greater improvement of KES was observed in the CS group (P = 0.003). Maximum walking speed (CS 4.7%, HB 1.8%; P = 0.001) and timed up‐and‐go (CS −4.7%, HB −0.2%; P < 0.001) significantly improved in the CS group only. Conclusions The intervention was effective in preventing sarcopenia and/or frailty. Most physical functions and MT improved after both interventions. The HB intervention is cost‐effective and may help prevent sarcopenia and/or frailty in the large older population.